Power quality improvement using fuzzy logic controlled voltage source PWM rectifiers. (2017) - Boukadoum, Aziz; Bahi, Tahar; Bouguerne, Abla
In the last years, many papers about research on PWM rectifiers have been published, these converters are widely used in power electrical networks, wind and solar power AC-DC interfacing, and in many other industry applications. In this paper, the direct current control based on hysteresis fuzzy logic controlled three-phase voltage source PWM rectifier for eliminating harmonics and compensating reactive power simultaneously in a power system is presented. A detailed mathematical model of the system is described and analysed. The proposed strategies are used to obtained nearly sinusoidal input current, low harmonics distortion (THD), improve the power factor at the unity, regulation of DC-link voltage at the required level with better responses and excellent performance. Simulation results show the effectiveness of the proposed strategy.